As competências clínicas para as diferentes terapias comportamentais - Vilares, João Eduardo Cattani (2022)
Since its emergence in the 1950s, Behavior Therapy has presented a series of internal divergences. In the United States, it has been proposed that behavioral therapies should be organized as waves. Each wave covers a series of approaches and acronyms based on different theoretical assumptions. Despite the difficulties of a direct comparison between American and Brazilian psychotherapeutic proposals, it is known that American approaches exert several influences on Brazilian psychotherapists. This influence of different approaches has led researchers to claim that the area may end up even more fragmented. This study analyzed the manuals of different behavioral-based psychotherapies, through the light of training based on competencies found in the literature and clarified what has been taught to psychotherapists by the proponents of different American proposals (Functional-Analytical Psychotherapy, Dialectical Behavior Therapy and Acceptance and Commitment Therapy) and Brazilian (Behavioral-Analytical Therapy and Reinforcement Contingency Therapy). The competencies for each one of the proposals were compiled, and the result demonstrated that the central aspects of the approaches are similar (e.g., environmental determinism, case assessment and intervention). The differences noted were in the authors’ style and in the theoretical aspects emphasized, such as the philosophy of science and case formulation. This knowledge can facilitate the development of curricula, complement studies of clinical processes, and provide a critical view for those who propose themselves to become behavioral therapists nowadays.